Application of foresighting approach in policy making to promote the circular economic model - Nguyen Hong Quan; Bach Tan Sinh; Le Ba Nhat Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Addressing the challenges of inclusivity and sustainability in the context of the 2030 Agenda for Sustainable Development requires: (a) broaden the strategic focus of science, technology and innovation policy (STI) to mainstream social challenges into the core of the Program; (b) mainstreaming the direct and indirect contributions of innovations to the economic, social and environmental aspects of sustainable development; and (c) promote transformative innovations with the potential to replace existing unsustainable systems and practices. The article provides international experience in applying the foresighting approach to STI policymaking in the direction of promoting transformative innovations with the potential to replace the traditional growth economic model to a circular economy model. Based on analyzing the status of the application of the foresight approach in Vietnam and international experience, the article proposes some solutions to further promote the application of the foresight approach in Vietnam in the context of Vietnam’s transform of its economic model towards a circular and environmentally friendly direction. Code: 22060601